Kesepadanan Tekstual dan Ideologi Penerjemahan Arab-Jawa dalam Kitab Shará¸¥ al-á¸¤ikam - Anis, Muhammad Yunus (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
This study attempts to elaborate textual equivalence of the Arabic translation and the Javanese translation in Ibn ?A??? Allah al-Sakandar??s masterpiece, al-?ikam. Within the first stage, the texts in this book will be studied from a number of linguistic aspects which are connected to lexical forms and phraseological feature. Every language is semantically assumed as possessing specific characteristic in terms of its lexical and phraseological features. The Sufis, in this case, will have particular inclination in their language expression. The lexical and phraseological features become, among others, a measure-ment of mystical language which covers compositional and unitary meanings. To comprehensively understand the mystical life explained in al-?ikam we need, therefore, to deeply study such lexical and phraseological features. The second stage will focus on the ideology of translation of al-?ikam. This sort of ideology will provide us information on the relation of the Indonesian Islamic texts and?along with their potential integration with?scholars around the world. The study finds that the ideology of translation has been founded on foreignization method and domestication method. These two methods have played a pivotal role on how particular texts of Sufisme are produced and consumed by the Indonesian Muslim society.